PENGEMBANGAN MEDIA BOARDBOOK BERBASIS METODE KONTEKSTUAL PADA SUBTEMA KEWAJIBAN DAN HAKKU DI RUMAH DI KELAS III SDN 066057 MEDAN DENAI - Putri Nurjannah; Irfan Dahnial (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study is motivated by the perception that the PPKn learning process is lacking in interest, deemed trivial, monotonous, and associated with other undesirable aspects. The class III teacher at elementary school of 066057 Medan Denai believes that students' lack of interest in learning about PPKn is attributed to the limited use of learning media, specifically relying solely on printed materials such as textbooks. This lack of diversity in learning materials results in decreased enthusiasm and boredom among students during their studies. The objective of this study is to create a Boardbook media using contextual methodologies in order to assess the viability of a product based on the validation of instruments. This study focuses on research and development (R&D) using a modified version of Thiagarajan and Semmel's 4D model, which has been simplified to a 3D model consisting of defining, designing, and creating. The study findings indicate that the Boardbook media, which is based on contextual approaches and focuses on my responsibility and rights at home in class III primary school of 066057 Medan Denai, has been verified by professional media validators. The findings were derived from a product feasibility percentage of 90.90%, which falls inside the